2020
DOI: 10.1186/s13063-020-04643-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dexamethasone treatment for patients with the acute respiratory distress syndrome caused by COVID-19: study protocol for a randomized controlled superiority trial

Abstract: Background: There are no specific generally accepted therapies for the coronavirus disease 2019 (COVID-19). The full spectrum of COVID-19 ranges from asymptomatic disease to mild respiratory tract illness to severe pneumonia, acute respiratory distress syndrome (ARDS), multisystem organ failure, and death. The efficacy of corticosteroids in viral ARDS remains unknown. We postulated that adjunctive treatment of established ARDS caused by COVID-19 with intravenous dexamethasone might change the pulmonary and sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 33 publications
1
53
1
4
Order By: Relevance
“…The major pharmaceuticals being evaluated include the antiviral agent remdesivir, interferon B-1a, monoclonal antibodies against interleukin 6 (IL-6) and IL-4, and dexamethasone. Dexamethasone ( Villar et al, 2020 ) and remdesivir ( Beigel et al., 2020 ) have shown efficacy in randomized controlled trials. Interestingly, administration of prednisolone, a glucocorticoid-like dexamethasone, showed a time-of-day-dependent effect in alleviating rheumatoid arthritis symptoms ( Buttgereit et al, 2008 ).…”
Section: Circadian Biology In Drug Development and Testingmentioning
confidence: 99%
“…The major pharmaceuticals being evaluated include the antiviral agent remdesivir, interferon B-1a, monoclonal antibodies against interleukin 6 (IL-6) and IL-4, and dexamethasone. Dexamethasone ( Villar et al, 2020 ) and remdesivir ( Beigel et al., 2020 ) have shown efficacy in randomized controlled trials. Interestingly, administration of prednisolone, a glucocorticoid-like dexamethasone, showed a time-of-day-dependent effect in alleviating rheumatoid arthritis symptoms ( Buttgereit et al, 2008 ).…”
Section: Circadian Biology In Drug Development and Testingmentioning
confidence: 99%
“…It is used to treat COVID‐19, but is teratogenic and must not be administered during the early phase of pregnancy 12 . When dexamethasone is administered concomitantly with standard therapy for COVID‐19 patients with moderate‐to‐severe acute respiratory distress syndrome, the number of days of artificial ventilation, up to day 28 of treatment (i.e., days in which the patient is alive and mechanical ventilation is not used), increases in comparison with standard therapy alone 13 . Corticosteroids have anti‐inflammatory effects and may prevent or suppress harmful inflammatory reactions that may lead to lung damage and/or multiple organ failure 14 .…”
Section: Discussionmentioning
confidence: 99%
“…( 1 , 13 ). Indeed, the RECOVERY trial showed that patients suffering from the most severe COVID-19 symptoms and were on respiratory support had the best responses to glucocorticoid treatment ( 1 , 13 , 14 ). However, as pointed out by RECOVERY, the same treatment is not beneficial, and possibly even harmful, during the early stages of the disease when a natural antiviral response is required.…”
Section: Corticosteroidsmentioning
confidence: 99%